Campanula martinii (Campanulaceae), a new species from northern Italy - Fenaroli, Franco; Pistarino, Annalaura; Peruzzi, Lorenzo; Cellinese, Nico (Phytotaxa, 2013)
Campanula martinii a new species in the C. rotundifolia species complex, is here described. C. martinii is seemingly endemic to dolomitic cliffs and rocky places of the Prealps in Lombardia and Trentino-Alto Adige (northern Italy). The plants are robust with long hypogeal stolons, papillose ovary and patent to reflexed calyx teeth. This species is hexaploid with chromosome number 2n = 102. The taxonomic and phylogenetic placement of the new species is briefly discussed.